دور التخطيط الاستراتيجي في تحسين الاتصال بين العمال في المؤسسة الاقتصادية دراسة حالة مؤسسة بوقرنين بتيم - إكرام زهاني; نسيمة زغيدي; نبيل بالساسي (جامعة الوادي university of eloued, 2024)
هدفت هذه الدراسة إلى معرفة دور التخطيط الاستراتيجي في تحسين الاتصال بين العمال في المؤسسة حيث أجريت الدراسة في مؤسسة بوقرنين بتيم، وتم استخدام الاستبيان كأداة لجمع البيانات وقد تم توزيعها على عينة متكونة من 104 عامل واسترجعت منها 66 استمارة وبعد الفرز تبين أنه 65 استمارة قابلة للمعالجة, ولتحليل البيانات واختبار فرضيات الدراسة تم استخدام برنامج الحزمة الإحصائية للعلوم الاجتماعية ‏SPSS، ومن خلال الدراسة تم الوصول إلى جملة من النتائج أهمها أن التخطيط الاستراتيجي عامل أساسي في بناء علاقة التواصل وتعزيز التفاهم بين العمال التخطيط الاستراتيجي يساهم في تحسين الاتصال في العمال في المؤسسة، وجود علاقة بين التخطيط الاستراتيجي والاتصال This study aimed to find out the role of strategic planning in improving communication among workers in the organization, the study was conducted at the Bouguernine Batim foundation, the questionnaire was used as a tool collecting data, it was distributed to a body consisting of 104 workers, and 66 questionnaires were retrieved from them, and after sorting it turned out that there were 65 questionnaires, it can be processed, and to analyze the data and test the study hypotheses, the statistical pockage for the social sciences (SPSS) program was used. Through the study, a number of results were reached, the most important of which is that strategic planning is an essential factor in building the communication relationship and enhancing understanding between workers, strategic planning contributes to improving communication between workers in the organization, there is a relationship between strategic planning and communication.
Keywords: التخطيط الاستراتيجي، الاتصال، تحسين الاتصال، مؤسسة بوقرنين بتيم strategic planning; communication; communication improvement; Bouguernine Batim foundaton.